Pandangan Ulama Kecamatan Amuntai Tengah Kabupaten Hulu Sungai Utara Mengenai Batasan Kewajiban Taat Seorang Istri Kepada Suami Yang Tidak Melaksanakan Ajaran Agama - Tri Widia Wati; Naila Khalidah (PT. AHLAL PUBLISHER NUSANTARA, 2025)
Nusyuz is more commonly known as a wife's disobedience to her husband, which gives the impression that it is one-sided, as though only the wife can disobey. In practice, however, disobedience can occur in both directions, from either the husband or the wife. If a husband fails to fulfill his responsibilities without a valid reason according to Sharia law, he is also considered nusyuz because of neglecting his responsibilities and failing to meet his rights and duties as the head of the household. This research aims to understand the views of scholars from Amuntai Tengah District regarding the limits of a wife's duty of obedience to a husband who does not practice religious teachings. The research method used is a descriptive qualitative approach, with data collection techniques including observation, interviews, and documentation. Data processing involved techniques such as data reduction, data display, and data verification. The results of the study show that several scholars believe the limits of a wife's obligation to obey her husband in Islam are clear. This obedience is conditional, meaning it only applies in matters that do not contradict Islamic law. A husband is considered nusyuz if, when advised by his wife, he restricts her and always becomes angry, using harsh words. However, a wife is allowed to advise a husband who does not follow religious teachings, and if the husband disregards her advice, she must be patient in providing counsel. This study recommends that husbands take responsibility for their obligations and duties toward their wives in order to build a sakinah mawaddah warahmah family. Keywords: Husband's Nusyuz, Husband's Responsibilities, Wife's Responsibilities Abstrak Nusyuz lebih dikenal sebagai pembangkangan istri terhadap suami, yang memberikan kesan searah, seolah-olah hanya istri yang bisa membangkang. Padahal dalam praktiknya, pembangkangan bisa terjadi dari dua arah, baik suami maupun istri. Apabila seorang suami tidak dapat memenuhi tanggung jawabnya tanpa alasan yang sah menurut syariat maka suami tersebut juga dianggap nusyuz karena lalai terhadap tanggung jawabnya dan tidak dapat memenuhi hak dan kewajibannya sebagai kepala rumah tangga. Penelitian ini bertujuan untuk mengetahui pandangan Ulama Kecamatan Amuntai Tengah mengenai batasan kewajiban taat seorang istri terhadap suami yang tidak melaksanakan ajaran agama. Metode penelitian yang digunakan adalah pendekatan kualitatif deskriptif, dengan Pengumpulan data dilakukan teknik observasi, wawancara dan dokumentar. Sedangkan pengolahan data menggunkan teknik reduksi data, display data dan verifikasi data. Hasil penelitian menunjukkan pandangan beberapa ulama bahwa batasan kewajiban taat seorang istri kepada suami dalam islam adalah kewajiban taat seorang istri kepada suami dalam islam memilki batasan yang jelas. Ketaatan ini bersifat bersyarat, yaitu hanya dalam perkara yang tidak bertentangan dengan syariat islam. dan seorang suami nusyuz kalau dinasihati seorang istri pasti dia mengkekang dan selalu marah-marah dan berbuat kelakuan kata-kata keras. Tetapi seseorang istri boleh memberi nasehat kepada suami yang tidak melaksanakan ajaran agama kalau suami yang menghiraukan nasehat seorang istri harus mempunyai sifat sabar untuk manasehat seorang suami yang menghiraukan nasehat seorang istri. Penelitian ini merekomendasikan perlunya suami bertanggung jawab terhadap hak-hak kewajiban kepada istri untuk membangun keluarga sakinah mawaddah warahmah. Kata Kunci: Nusyuz Suami, Kewajiban Suami, Kewajiban Istri